Efficiency evaluation of China's investment in Africa under the background of constructing "Silk Road Economic Belt": Application of DEA model and Malmquist index method - Tian Ze; Fan Yumei; Liu Chao (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
In recent years, with implementation and propulsion of the strategic planning "One Belt and One Road" of China, quality and efficiency of China's foreign direct investment have increasingly become a focused issue. This paper utilizes the DEA model and Malmquist index method to select the data of China's investment in 20 countries of Africa and conducts the empirical research on dynamic evaluation of efficiency of China's direct investment in Africa. The result shows that the general efficiency of China's direct investment in Africa is in a declined fluctuation trend, while the technical efficiency of the investment is in a constant rising trend, and direct investment in most host countries has reached or is reaching the optimal scale. From the perspective of country difference, the efficiency of direct investment in a small number of host countries has been improved while that in most host countries has declined. With improvement of African countries in absorbing and utilizing foreign technologies and management level and effective innovation of China's direct investment in host countries, the efficiency of direct investment in host countries will be constantly improved. The suggestions such as optimizing investment location selection, emphasizing on the linkage between support facilities and industrial chain of the investment project, improving technology spillover efficiency and enhancing infrastructure investment are proposed.
Keywords: 330; Africa; foreign direct investment; efficiency evaluation; DEA; Malmquist index; Silk Road Economic Belt